Interval Value Fuzzy k-Ideals of a KU-Semigroup - Talib, Sally A.; Kareem, Fatema F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The notion of interval value fuzzy k-ideal of KU-semigroup was studied as a generalization of afuzzy k-ideal of KU-semigroup. Some results of this idea under homomorphism are discussed. Also, we presented some properties about the image (pre-image) for interval~ valued fuzzy~k-ideals of a KU-semigroup. Finally, the~ product of~ interval valued fuzzyk-ideals is established.